2021
DOI: 10.1073/pnas.2106535118
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new SARS-CoV-2 variant that emerged in Brazil

Abstract: The spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) plays a key role in viral infectivity. It is also the major antigen stimulating the host's protective immune response, specifically, the production of neutralizing antibodies. Recently, a new variant of SARS-CoV-2 possessing multiple mutations in the S protein, designated P.1, emerged in Brazil. Here, we characterized a P.1 variant isolated in Japan by using Syrian hamsters, a well-established small animal model for the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 25 publications
3
61
0
3
Order By: Relevance
“…Therefore, Syrian hamsters can be used for research on viral transmissibility. At present, the replicative abilities, pathogenicity, transmissibility, and susceptibility to neutralization of some virus variants (P.1, D614G, and a variant with a deletion at the S1/S2 junction of the spike protein) have been evaluated in hamsters ( Hou et al, 2020 ; Imai et al, 2021 ; Plante et al, 2021 ; Wang et al, 2021 ).…”
Section: Hamstermentioning
confidence: 99%
“…Therefore, Syrian hamsters can be used for research on viral transmissibility. At present, the replicative abilities, pathogenicity, transmissibility, and susceptibility to neutralization of some virus variants (P.1, D614G, and a variant with a deletion at the S1/S2 junction of the spike protein) have been evaluated in hamsters ( Hou et al, 2020 ; Imai et al, 2021 ; Plante et al, 2021 ; Wang et al, 2021 ).…”
Section: Hamstermentioning
confidence: 99%
“…Species that are generally susceptible to SARS-CoV-2 are listed in red, marginally susceptible species are listed in cyan, and generally resistant species are listed in blue. * Experimental evidence showed that wild-type mice ( Mus musculus ) are susceptible to mouse-adapted SARS-CoV-2 isolates or certain variants of concern (VOC) that contain an N501Y substitution in the spike protein [ 138 , 139 , 140 , 141 ] In contrast, gene-edited mice expressing the human angiotensin-converting enzyme 2 (hACE2) receptor are highly susceptible to infection with ancestral and variant SARS-CoV-2 strains [ 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. ** Cottontail rabbits ( Sylvilagus sp.)…”
Section: Introductionmentioning
confidence: 99%
“…According to the last epidemiological bulletin of the Amazonas state, Manaus recorded 194,957 COVID-19 cases, 9263 deaths, and a lethality rate of 4.8% [33]. Moreover, several SARS-CoV-2 VOCs circulate broadly in Brazil [34,35]. VOCs are SARS-CoV-2 lineages associated with increased transmissibility and severity and decreased vaccination effectiveness in humans.…”
Section: Discussionmentioning
confidence: 99%